“The United States in Syria. Why it still matters?” - Saidbek Mamasoliev (Periodica Journal, 2024)
The US mission in Syria is hampered with numerous barriers necessitating a novel approach or change in President Joe Biden's administration strategy. The leadership of Syria is unwilling to compromise or reform. Syrian's lip service exposes United States (US) and puts them between a rock and a hard place. Syria's unwillingness to comply can lead to suspension of America, snapback sanctions and loss of European incentives. President Joe Biden has inherited Syrian Crisis, and it distresses that have lasted a decade (since 2011). The Syrian Crisis poses humanitarian and strategic hurdles for the novice US administration. The Syrian government is responsible for the loss of millions of Syrians' lives and the destruction of properties since the onset of the conflict in 2011 (Cloud 2021). However, it is not yet time to throw in the towel yet since the US has a chance to re-evaluate US policy in Syria and prioritize diplomacy to advance its interests in the region.
Keywords: US; Syria; Russia; ISIS